SIMULASI DALAM MANAJEMEN PENGAMBILAN KEPUTUSAN MENGGUNAKAN AHP - Yusuf Amrozi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2017)
Management Decision-Making is the function of management on organizational decision support. In the curent situation, the system is generally supported by the Information Technology. There are three sub-management, we called: management modeling, database management and communication management systems. The Model is used to find the optimum formulation to solve existing problems. Database management systems serves as collect of data that information would be processed. The communication system enables the decision makers how to communicate among the system to make optimum decision. The paper elaborates Decision management and simulation of management support system using Analytical Hierarchy Process model, in case how to select new employee on the Faculty of Science and Technology, State Islamic University (UIN) Sunan Ampel Surabaya.